Artificial Intelligence Based Identification of the Attitude Dynamics for a Quadrotor UAV - Avdeev, Alexander (2014)
A Master of Science thesis in Mechatronics Engineering by Alexander Avdeev entitled, "Artificial Intelligence Based Identification of the Attitude Dynamics for a Quadroto UAV," submitted in December 2014. Thesis advisor is Dr. Khaled Assaleh and thesis co-advisor is Dr. Mohammad Abdel Kareem Rasheed Jaradat. Available are both soft and hard copies of the thesis.